캐러웨이(Carum carvi) 분말을 첨가한 설기떡의 품질특성 및 생리활성 - 장문정(Munjeong Jang); 한인화(Inhwa Han) (한국식품과학회지, 2023)
The quality characteristics and physiological activities of Sulgidduks prepared using caraway powder (0, 1, 3, 5, and 7%) were examined. The pH and L values decreased and sugar content, a and b values, and total color difference of Sulgidduks increased with the addition of caraway. Hardness and springiness increased and cohesiveness, gumminess, chewiness, and resilience decreased. The total polyphenol and flavonoid contents of the Sulgidduks extracts with water or 80% ethanol increased with the addition of caraway and those were higher in the water extract than in the 80% ethanol extract. DPPH and ABTS radical scavenging activities also increased and those were higher in the 80% ethanol extract than in the water extract. The reducing power and lipase inhibitory activity increased in both water and 80% ethanol extracts but SOD-like activity increased only in the water extracts. These results will supply basic information for the usage of caraway to develop healthy food. KCI Citation Count: 0